2008
DOI: 10.1063/1.2993168
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ray tracing for internal waves. II. Finite-amplitude effects

Abstract: We examine the transmission of small and moderately large internal gravity wavepackets through uniformly and nonuniformly stratified fluids using fully nonlinear numerical simulations. The simulations of finite-amplitude waves in a uniformly stratified fluid show that the weakly nonlinear theory developed for horizontally periodic wavepackets extends well to the dynamics of wavepackets with horizontal extent comparable to the horizontal wavelength. In simulations of small-amplitude wavepackets in a nonuniforml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“… Sutherland [1996, 1999, 2000] numerically investigated the reflection and transmission of internal waves under the wave propagation distance smaller than the density scale height by using a set of nonlinear 2‐D motion equations which showed that if the amplitude of wave packet was large, nonlinear effects could significantly enhanced the transmission of wave packet across the reflecting level as a result of the effective mean flow induced by the wave. For finite‐amplitude waves in a nonuniformly stratified fluid, the simulation showed that the transmission coefficient exhibits a monotonic increase as a function of the incident wave amplitude but little dependence on the wavepacket extent [ Brown et al , 2008]. However, the nonlinear physical process of atmospheric gravity wave reflection in the atmospheric jets is not quite clear.…”
Section: Introductionmentioning
confidence: 99%
“… Sutherland [1996, 1999, 2000] numerically investigated the reflection and transmission of internal waves under the wave propagation distance smaller than the density scale height by using a set of nonlinear 2‐D motion equations which showed that if the amplitude of wave packet was large, nonlinear effects could significantly enhanced the transmission of wave packet across the reflecting level as a result of the effective mean flow induced by the wave. For finite‐amplitude waves in a nonuniformly stratified fluid, the simulation showed that the transmission coefficient exhibits a monotonic increase as a function of the incident wave amplitude but little dependence on the wavepacket extent [ Brown et al , 2008]. However, the nonlinear physical process of atmospheric gravity wave reflection in the atmospheric jets is not quite clear.…”
Section: Introductionmentioning
confidence: 99%
“…This analytic study was extended to examine the influence of shear [17]. Further numerical studies examined the transmission of waves through more complex stratification [18][19][20][21][22] and large-amplitude effects were also considered [23]. However, in all these studies except Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the parameters of the sponge layer are L sponge ¼ 5 m and s sponge ¼ 500 s for the layer length scale and decay time scale (26). We omit the upper and lower 25 m (192 grid points) of the domain from our analysis (Fig.…”
Section: A Model Setupmentioning
confidence: 99%
“…Therefore, we follow a similar procedure as in Ref. 26 and modify the initial velocity field so that the total horizontal momentum of the wave group times the vertical component of the group velocity is equal to the net momentum flux of the wave group. This is equivalent to adding an approximation of the pseudomomentum to the velocity at every point.…”
Section: B Initial Conditionsmentioning
confidence: 99%